Operations of Austrian Armed Forces (AAF) within law-enforcement assistance operation for Critical Infrastructure Protection using the example of Vienna International Airport - Stumpf Andreas (2017)
Global conflicts and crises are dominating factors in policy. Nowadays the security situation with current forms of threats all over the world is a challenge. Migration and terrorism are causing dangers that can only be managed with international and comprehensive measures. Besides conventional threats, actual conflicts may affect security policy in Austria by international terrorism, illegal migration, organised crime and terrorist attacks on strategic infrastructure. The focus of this thesis lies however on the protection of critical infrastructure in Austria. Therefore, regulations, responsible authorities and agencies will be outlined based on the Austrian Program for Critical Infrastructure Protection. Furthermore, legal regulations for law-enforcement assistance operations of Austrian Armed Forces are listed as a basis for all follow-up actions. Security measures at airports, security services and cooperation with public authorities are explained by taking the example of Vienna International Airport. Finally, capabilities and tasks for units of Austrian Armed Forces in assistance operations for the protection of critical infrastructure are amplified.